2020
DOI: 10.1029/2019jd031498
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical Effects of Water Content and Temperature on the Triboelectrification of Volcanic Ash on Long Time Scales

Abstract: The triboelectrification of ash in low-energy collisions is modulated by humidity 8 and temperature on long timescales 9• The amount of electrostatic charge gained by ash through triboelectric processes is reduced in wet environments over minute-long timescales• The reduction in triboelectric charging efficiency in humid environments suggests that other electrification mechanisms dominate in maturing columns

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…Such global lightning detection data was used during the response to the eruption of the remote, and under-instrumented Bogoslof volcano in Alaska (Coombs et al, 2018), where lightning was detected from only roughly half of the ash-producing eruptions. Van Eaton et al (2020) showed that secondary ice-charging processes (Arason et al, 2011;Behnke et al, 2013;Van Eaton et al, 2016;Woodhouse & Behnke, 2014), rather than ash-charging processes (e.g., Houghton et al, 2013;James et al, 2000;Mendez Harper & Dufek, 2016;Mendez Harper et al, 2020;Stern et al, 2019), were likely responsible for the lightning detected by the global networks, and speculated that it was very likely that there was much more lightning and electrical activity that occurred that wasn't detected by the long-range VLF sensors. During this eruption, the global lightning data was a boon for the volcano response effort, though the latency between eruption and first lightning detection varied from one minute to one hour.…”
mentioning
confidence: 99%
“…Such global lightning detection data was used during the response to the eruption of the remote, and under-instrumented Bogoslof volcano in Alaska (Coombs et al, 2018), where lightning was detected from only roughly half of the ash-producing eruptions. Van Eaton et al (2020) showed that secondary ice-charging processes (Arason et al, 2011;Behnke et al, 2013;Van Eaton et al, 2016;Woodhouse & Behnke, 2014), rather than ash-charging processes (e.g., Houghton et al, 2013;James et al, 2000;Mendez Harper & Dufek, 2016;Mendez Harper et al, 2020;Stern et al, 2019), were likely responsible for the lightning detected by the global networks, and speculated that it was very likely that there was much more lightning and electrical activity that occurred that wasn't detected by the long-range VLF sensors. During this eruption, the global lightning data was a boon for the volcano response effort, though the latency between eruption and first lightning detection varied from one minute to one hour.…”
mentioning
confidence: 99%
“…Charging in volcanic plumes may also be actively detected using satellite GNSS networks such as GPS (Méndez Harper et al 2019 ). Dense plumes of volcanic ash can attenuate GPS signals, providing information on microphysical and charge properties of the plumes (Aranzulla et al 2013 ; Larson 2013 ; Grapenthin et al 2018 ).…”
Section: Detection and Characteristics Of Volcanic Lightningmentioning
confidence: 99%
“…Explosive eruptions eject massive quantities of fine ash (<63 μm) into the atmosphere and can be accompanied by volcanic lightning near the vent, within the overlying jet (Aizawa et al., 2016; Behnke et al., 2011, 2014; Cimarelli et al., 2016; McNutt & Williams, 2010; Woodhouse & Behnke, 2014). Experiments (Cimarelli et al., 2014; Forward et al., 2009; Gaudin & Cimarelli, 2019a; James et al., 2000; Méndez Harper & Dufek, 2016; Méndez‐Harper et al., 2015, 2020; Stern et al., 2019b; Vossen et al., 2021) and observations (Aizawa et al., 2016; Behnke et al., 2011, 2014, 2018; Behnke & McNutt, 2014; Cimarelli et al., 2016; Haney et al., 2020) suggest that the occurrence, frequency and intensity of electrical discharges near the vent and within the overlying ash column are sensitive to the concentration of fine ash and the character of underlying mechanisms of particle‐particle collisions and charge transfer (Behnke & Bruning, 2015; Bruning & MacGorman, 2013; Smith et al., 2018). Within the ash columns, this momentum exchange is also diagnostic of turbulent entrainment and mixing properties (Behnke & Bruning, 2015) that govern the rise and gravitational stability of eruption columns (Gilchrist & Jellinek, 2021; Woods, 2010).…”
Section: Introductionmentioning
confidence: 99%